KRIBB11: A Promising Drug that Promotes Microglial Process Elongation and Suppresses Neuroinflammation - Su, Jianbin; Dou, Zhihua; Hong, Hongxiang; Xu, Feng; Lu, Xu; Lu, Qun; Ye, Ting; Huang, Chao (Frontiers in Pharmacology, 2022)
Microglia are key components of the central innate immune system. The over-activation of microglia, which occurs in nervous system disorders, is usually accompanied with retractions of their ramified processes. Reversing of microglial process retraction is a potential strategy for the prevention of neuroinflammation. Our previous studies have reported some endogenous molecules and drugs that can promote microglial process elongation at conditions in vitro and in vivo, such as butyrate and β-hydroxybutyrate, sulforaphane, and diallyl disulfide. Here, reported another compound that can promote microglial process elongation. We found that KRIBB11, a compound which has been reported to suppress nitric oxide production in microglia, induced significant elongations of the processes in microglia in cultured and in vivo conditions in a reversible manner. KRIBB11 pretreatment also prevented lipopolysaccharide (LPS)-induced shortenings of microglial process in cultured conditions and in vivo conditions, inflammatory responses in primary cultured microglia and the prefrontal cortex, and depression-like behaviors in mice. Mechanistic studies revealed that KRIBB11 incubation up-regulated phospho-Akt in cultured microglia and Akt inhibition blocked the pro-elongation effect of KRIBB11 on microglial process in cultured conditions and in vivo conditions, suggesting that the regulatory effect of KRIBB11 is Akt-dependent. Akt inhibition was also found to abrogate the preventive effect of KRIBB11 on LPS-induced inflammatory responses in primary cultured microglia and prefrontal cortexes as well as LPS-induced depression-like behaviors in mice. Collectively, our findings demonstrated that KRIBB11 is a novel compound that can prevent microglial activation and neuroinflammation-associated behavioral deficits possibly through inducing the Akt-mediated elongation of microglial process.